Determination of dynamic ankle ligament strains from a computational model driven by motion analysis based kinematic data - Wei, F.; Braman, J. E.; Weaver, B. T.; Haut, R. C. (Journal of Biomechanics, 2011)
External rotation of the foot has been implicated in high ankle sprains. Recent studies by this laboratory, and others, have suggested that torsional traction characteristics of the shoe-surface interface may play a role in ankle injury. While ankle injuries most often involve damage to ligaments due to excessive strains, the studies conducted by this laboratory and others have largely used surrogate models of the lower extremity to determine shoe-surface interface characteristics based on torque measures alone. The objective of this study was to develop a methodology that would integrate a motion analysis-based kinematic foot model with a computational model of the ankle to determine dynamic ankle ligament strains during external foot rotation. Six subjects performed single-legged, internal rotation of the body with a planted foot while a marker-based motion analysis was conducted to track the hindfoot motion relative to the tibia. These kinematic data were used to drive an established computational ankle model. Ankle ligament strains, as a function of time, were determined. The anterior tibiofibular ligament (ATiFL) experienced the highest strain at 9.2±1.1%, followed by the anterior deltoid ligament (ADL) at 7.8±0.7%, averaged over the six subjects. The peak ATiFL strain occurred prior to peak strain in the ADL in all subjects. This novel methodology may provide new insights into mechanisms of high ankle sprains and offer a basis for future evaluations of shoe-surface interface characteristics using human subjects rather than mechanical surrogate devices.